2014
DOI: 10.1002/jgt.21801
|View full text |Cite
|
Sign up to set email alerts
|

Graphs with Few 3‐Cliques and 3‐Anticliques are 3‐Universal

Abstract: For given integers k, l we ask whether every large graph with a sufficiently small number of k-cliques and k-anticliques must contain an induced copy of every l-vertex graph. Here we prove this claim for k = l = 3 with a sharp bound. A similar phenomenon is established as well for tournaments with k = l = 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 26 publications
(58 reference statements)
1
15
0
Order By: Relevance
“…In [8] we initiated the study of 4-local profiles of tournaments, namely the set P = {(t 4 (T ), c 4 (T ), w(T ), l(T ))|T is a family of tournaments for which all the limits exist} ⊆ R 4 .…”
Section: A Notationmentioning
confidence: 99%
“…In [8] we initiated the study of 4-local profiles of tournaments, namely the set P = {(t 4 (T ), c 4 (T ), w(T ), l(T ))|T is a family of tournaments for which all the limits exist} ⊆ R 4 .…”
Section: A Notationmentioning
confidence: 99%
“…Note that our definition of -universal sequences is slightly different from the one given in [10]. The latter required additionally that p H (G k ) be bounded away from 0 for each H of order .…”
Section: Question 12 ([10]mentioning
confidence: 99%
“…The next lemma and its corollary can be viewed as a strengthening of the 3-universality result from [10] (although, unlike Linial and Morgenstern, we do not optimize the error term ε). It provides additional information about the 3-local profile of Goodman graphs, asserting that it is determined completely by p 0 (and, equivalently, by p 3 ).…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Goodman [6] also conjectured the maximum of t 0 + t 3 amongst the graphs with a given number of edges, which was later proved by Olpp [13]. More recently, Linial and Morgenstern [10] showed that every sequence of graphs with t 0 + t 3 asymptotically minimal is 3-universal. Hefetz and Tyomkyn [7] then proved that such sequences are 4-universal, but not necessarily 5-universal, and moreover that any sufficiently large graph H can be avoided by such a sequence.…”
Section: Introductionmentioning
confidence: 95%